Investigation of treatment with molnupiravir and immune stimulants for use in the management of feline infectious peritonitis and associated comorbidities - Cerna, Petra, author; Lappin, Michael R., advisor; Dow, Steven, advisor; Santangelo, Kelly, committee member; Dean, Gregg, committee member (Colorado State University. Libraries, 2025)
Feline coronavirus (FCoV) belongs to the order Nidovirales; family Coronaviridae; subfamily Coronavirinae; genus Alphacoronavirus; species Alphacoronavirus 1. Feline coronavirus exists in two biotypes; feline enteric coronavirus (FECV), which mainly replicates in the enteric epithelial cells, and feline infectious peritonitis virus (FIPV), which results in lethal infection with efficient systemic replication in monocytes or macrophages. Efficient FCoV replication in activated monocytes and macrophages is a key event in feline infectious peritonitis (FIP) pathogenesis. Fortunately, only a small proportion of FCoV-infected cats go on to develop FIP which typically manifests as a vasculopathy resulting in ('effusive') form (up to 80% of FIP cases have effusions), or granuloma formation resulting in ('non-effusive') mass lesions, or a combination of the two. The effusive form of disease generally is believed to develop in cats with poor cell-mediated immune responses, and the non-effusive form develops in cats with partial cell-mediated immunity. Recently, new antiviral drugs like the nucleoside analog GS-441524 and molnupiravir (MPV) has been used in successful treatment of FIP. However, more treatment options for cats with FIP, especially those that not responding or relapse, are needed and the goal of this work was to evaluate the use of nucleoside analogue molnupiravir and immune stimulants to determine the best treatment protocols for cats with FIP. We compared two different immune stimulants for antiviral activity in cats: a TLR 2/6-activating compound polyprenyl immunostimulant; (PI) and a liposome Toll-like receptor 3/9 agonist complexes (LTC) to determine relative abilities to stimulate immune responses in vitro and to study the effects of treatment on immune responses in healthy cats. In these studies, both LTC and PI protocols induced immune enhancing effects, suggesting a possible clinical use for the management of chronic infectious diseases like FIP. We concluded that activating the TLR 3 and 9 pathways (LTC) induced superior broad interferon production in vitro than the activation of the TLR 2 and 6 pathways (PI). We also determined the pharmacokinetics of molnupiravir in cats with naturally occurring FIP by measuring MPV and EIDD-1931 (β-D-N4-hydroxycytidine; NHC) serum levels in seven cats diagnosed with naturally occurring FIP treated with MPV. The mean NHC concentrations at all time points were at least 4 times the reported in vitro EC50 for feline coronavirus strains and twice daily dosing for seven days did not lead to accumulation of drug within the serum. Minimal accumulation of drug was seen in trough concentrations following twice-daily dosing for 7 days. These results supported the use of MPV in the treatment of FIP. We have conducted a prospective, open‐label longitudinal single‐center clinical trial with MPV in cats with FIP. A total of 78% cats survived to 6 months and 22% cats died or were euthanized. We also found that the median total bilirubin concentrations were significantly different (p= 0.0007) between the survivors vs non-survivors. Relapses occurred in 12% of the cats and all achieved remission during a second course of treatment. No adverse effects necessitated discontinuation of the treatment. This study showed effectiveness of using 12 week therapy with MPV in treatment of FIP. While most cats with FIP were euthanized in the past; more cats are now being treated with antiviral drugs. As a result of this, new disease processes that could be associated with FIP are being recognized; for example, immune-mediated hemolytic anemia (IMHA), myocarditis or other cardiac changes, and other comorbidities and the goal of this study was to evaluate the development of IMHA and myocarditis in cats with FIP and its impact on survival and prognosis of these cats. We have evaluated 45 cats with associative IMHA to FIP in a multicentric study. The median hematocrit for these cats was 18% and anemia was non-regenerative in 36/45 cats with concurrent thrombocytopenia was present in 18/45 cats. All 45 cats were treated with nucleoside analogs and 44 cats with glucocorticoids and at the time of last follow-up 33 cats had survived while 12 had died or were euthanized. Although FIP is likely an uncommon cause of associative IMHA, as more cats with FIP are treated with antiviral therapy, it is important to consider IMHA as a possible cause of anemia in cats with FIP. We documented the cardiac changes in cats diagnosed with FIP using echocardiography and cardiac troponin I (cTnI). Twenty cats diagnosed with FIP and tested negative for concurrent infections associated with myocarditis underwent an echocardiographic examination. The left ventricular posterior wall from right parasternal long axis and short axis was thickened in 55% (11/20) and 25% (5/20) of cats, respectively. The median cTnI at initial evaluation was 0.37 ng/ml (IQR 0.20-0.83) and recheck of cTnI performed at 12 weeks following antiviral therapy in 6 cats that initially had elevated cTnI showed normalized cTnI to <0.20 ng/ml. Cats with FIP can present with elevations in cTnI and ventricular wall thickening, which are suggestive of myocarditis and/or myocardial injury. The results of the studies described the use of antivirals and immune stimulants in FIP and outlined the possible comorbidities clinicians will be facing during the FIP treatment. Further investigation into FIP treatment with antivirals such as nucleoside analogues and protease inhibitors and immune stimulants are needed to increase the success rate in treatment of critically ill cats and prevent relapses in the future. Moreover, studies evaluating comorbidities in cats with FIP such as IMHA, myocarditis, sepsis and gastrointestinal disease are needed to better understand how to manage these cases.